Allergen sensitization stratifies IL-31 production by memory T cells in atopic dermatitis patients - Sans-de San Nicolàs, Lídia; Figueras-Nart, Ignasi; García-Jiménez, Irene; Bonfill-Ortí, Montserrat; Guilabert, Antonio; Curto-Barredo, Laia; Bertolín-Colilla, Marta; Ferran, Marta; Serra-Baldrich, Esther; Pujol, Ramon M.; Santamaria-Babí, Luis F. (Frontiers in Immunology, 2023)
Background: The role of allergen sensitization in IL-31 production by T cells and specifically in the clinical context of atopic dermatitis (AD) has not been characterized. Methods: The response to house dust mite (HDM) in purified memory T cells cocultured with epidermal cells from AD patients (n=45) and control subjects (n=9) was evaluated. AD-associated cytokines from culture supernatants, plasma proteins and mRNA expression from cutaneous lesions were assessed and related with the clinical features of the patients. Results: HDM-induced IL-31 production by memory T cells defined two subsets of AD patients according to the presence or absence of IL-31 response. Patients in the IL-31 producing group were younger, showed a more inflammatory profile, and increased HDM-specific (sp) and total IgE levels compared to the IL-31 non-producing group. A correlation between IL-31 production and patient’s pruritus intensity, plasma CCL27 and periostin was detected. When the same patients were analyzed based on HDM-specific (sp) IgE and total IgE levels, an increased IL-31 in vitro response, as well as type 2 markers in plasma and cutaneous lesions, was found in patients with sp IgE levels > 100 kUA/L and total IgE levels > 1000 kU/L. The IL-31 response by memory T cells was restricted to the CLA+ T-cell subset. Conclusion: IgE sensitization to HDM allows stratifying IL-31 production by memory T cells in AD patients and relating it to particular clinical phenotypes of the disease.